2015
DOI: 10.1007/s00520-015-2740-7
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-associated bloodstream infections and thrombotic risk in hematologic patients with peripherally inserted central catheters (PICC)

Abstract: PICCs represent a useful and safe alternative to conventional CVAD for the management of patients with hematologic malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 20 publications
3
41
3
1
Order By: Relevance
“…A literature review by Chopra and colleagues 3 showed higher rates of PICC-related bloodstream infections among adult patients with cancer than among those without cancer (1.1/1000 catheter days v. 1.8-7.7/1000 catheter days). Morano and colleagues 18 reported on 612 patients with hematological disease with primarily (86.8% of patients) 4 French single-lumen distally valved silicone PICCs (Groshong [Bard Peripheral Vascular]); the incidence of catheter-related bloodstream infection was 7.7%, or 0.59/ 1000 catheter days, and the mean dwell time was 101 days.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review by Chopra and colleagues 3 showed higher rates of PICC-related bloodstream infections among adult patients with cancer than among those without cancer (1.1/1000 catheter days v. 1.8-7.7/1000 catheter days). Morano and colleagues 18 reported on 612 patients with hematological disease with primarily (86.8% of patients) 4 French single-lumen distally valved silicone PICCs (Groshong [Bard Peripheral Vascular]); the incidence of catheter-related bloodstream infection was 7.7%, or 0.59/ 1000 catheter days, and the mean dwell time was 101 days.…”
Section: Discussionmentioning
confidence: 99%
“…And they are easy to insert, and associated to a low rate of early and late complications compared to conventional percutaneous method. Furthermore, PICCs are also easy to remove and less expensive than some other devices 4, 5 . However, PICCs have their own risks, such as infection, phlebitis and thrombosis 6 .…”
Section: Introductionmentioning
confidence: 99%
“…These complications significantly decrease quality of life among patients and lead to additional expense. Serious thrombosis complications and PICC infections have been mostly studied (Del Principe et al., ; Morano et al., ; Yi et al., ). Previous studies demonstrated that lower incidence of catheter‐related bloodstream infection (CRBSI) was observed in patients with PICCs compared to other CVCs (Al Raiy et al., ; Gunst et al., ).…”
Section: Introductionmentioning
confidence: 99%